Subsidizing extinction?. Issue 1 (24th January 2020) - Dempsey, Jessica; Martin, Tara G; Sumaila, U. Rashid
Abstract: In 2010 world governments agreed to eliminate, phase out or reform incentives that harm biodiversity by 2020. Yet few governments have even identified such incentives, never mind taking action on them. While some subsidies are well studied, such as in fisheries and fossil fuel production, there is an urgent need for the conservation community to study the potential effects a broader array of subsidies have on biodiversity. In addition, we need a better understanding of who benefits from these subsidies. We term this pursuit 'subsidy accountability', which is crucial but challenging work crossing disciplines and government ministries. It requires ecologists, forensic accountants, and policy wonks, calculating and forecasting the positive and negative effects of subsidies and their elimination on biodiversity and vulnerable human populations. The Intergovernmental Panel for Biodiversity and Ecosystem Services recently concluded that action on biodiversity loss requires transformative economic change; true action on subsidies is one step towards such change.